EFEKTIFITAS PEMANFAATAN BATU ALAM BERSILIKA, SILANE, DAN VINYL SILANE SEBAGAI PENGISI BAHAN ISOLASI VAKUM KOMPOSIT RESIN EPOKSI UNTUK ISOLATOR LISTRIK - Moh Toni Prasetyo; Solechan Solechan (MEDIA ELEKTRIKA, 2017)
Insulation materials that commonly used in air insulation, which, is operated at high voltage, are the porcelain, glass, and polymer materials. One of the insulating polymer materials that are used is epoxy resin because it has several advantages compared to that. However, thisinsulation material has a degradation of the surface due to environmental and cause insulation coated with dirt and chemicals in the long time.  This research was conducted on resin epoxy by comparison of MPDA, DGEBA, and filler (stone and silane) with a percentage value of 10%; 20%; 30%; 40% and 50%, sample size 120 x 50mm. vinyl silane is mixed as a coupling agent of composite materials. Vacuum method to left outvoid.Research was done in laboratory according to standard IEC 587: 1984. In this study, the effect of variation in stoichiometry to the hydrophobic contact angle value, leakage current waveforms, and surface degradation caused by erosion and tracking processes and tracking time were analyzed. From the results of the research, it was obtained that the epoxy resin that was used in this research are categorized as hydrofobik and partially wetted. The increase concentration of silane dan Kukup coastal sand as filler caused the increase in contact angle which meant the increase insurface insulation resistance, so that leakage currents flew on the surface not easily and slow down the aging or the degradation decreasing on the surface of insulating material. Concentration value of filler that had the optimal performance of the tracking process and erosion was 40%. Keywords : angle of contact, epoxy resin, hidropobik, isolator, leaky current, materials filler